Biological Control and Plant Growth Promotion Properties of Volatile Organic Compound-Producing Antagonistic Trichoderma spp. - Joo, Jin Ho; Hussein, Khalid Abdallah (Frontiers in Plant Science, 2022)
Trichoderma is environmentally vital due to their plant growth-promoting effects (such as enhancement of nutrients supply, suppression of plant pathogens, and promotion of plant defense). Biogenic volatile organic compounds (VOCs) are diverse chemical substances emitted by Trichoderma spp. The potential role of VOCs in biological control and plant growth-promotion has recently been recognized. Here, the Trichoderma-VOCs' performance for plant growth-promotion and suppression of plant pathogens are evaluated. We further investigated VOC emission profiles of T. harzianum using GC–MS. The Trichoderma-VOCs exhibited significant (P < 0.05) antifungal properties against all tested pathogenic fungi. T. atroviride-VOCs showed a decisive inhibition to Alternaria panax, Botrytis cinerea, Cylindrocarpon destructans, and Sclerotinia nivalis. The germinating seeds demonstrated growth enhancement in the presence of Trichoderma-VOCs emitted by different strains. Low levels of cyclopentasiloxane, decamethyl, cyclotetrasiloxane, and octamethyl were found in T. harzianum KNU1 strain whereas cyclopentasiloxane, decamethyl, cyclotetrasiloxane, and octamethyl showed higher emission levels as Si-containing compounds. The results reveal the potentiality of VOCs as a biocontrol resource against deleterious rhizosphere microorganisms and underline the importance of Trichoderma-VOCs emissions in regulating plant growth and development.